UNDERSTANDING THE RELATIONSHIP BETWEEN HUMAN RESOURCES MANAGEMENT (HRM), HUMAN RESOURCES MANAGEMENT PRACTICES (HRMP) AND EMPLOYEE ENGAGEMENT - Kumar Kundu, Anjan (International Journal of Psychosocial Rehabilitation, 2024)
The connection between Human Resources Management Practices (HRMP) and employee engagement has acquired critical consideration structure researchers. Regardless of the significance of HRMP and its effect on employee engagement in the business, little examination has been done as far as developing a deliberate writing audit in the branch of knowledge. Subsequently, this paper intends to introduce a methodical writing survey of articles dependent on forty exceptionally positioned diaries during the time of 1990 to 2017. The paper researches the chronicled advancements of Human Resources Management (HRM), HRMP, and employee engagement to introduce the reasonable evolvement and elaboration of the connection among HRMP, and employee engagement. The writing featured that appropriately executing HRMP impacts employee engagement, and what this relationship decidedly means for the general presentation. In this term, a proposed system is introduced. At long last, the examination restrictions and roads for future analysts are given